DAMPAK SOSIAL MEDIA TERHADAP INTERAKSI SOSIAL PADA REMAJA: KAJIAN SISTEMATIK - Muhamad Ayub (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: This article reports the results of a systematic review of articles published between 2011 and 2021 that specifically examine the impact of social media on social interaction among adolescents. We used the google scholar database and articles published in SAGE and Sciencedirect. Articles from various databases were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The results of the analysis that social media can be useful and beneficial, especially for teenagers and students for self-development, getting new information, adding knowledge, adding networks. But it also creates distance from the individuals around them to affect the mental health of adolescents. Keywords: Adolescence, Impact Social Media, Social Interaction, Social MediaAbstrak: Artikel ini melaporkan hasil kajian sistematik tentang artikel-artikel yang diterbitkan antara tahun 2011 hingga 2021 yang secara khusus mengkaji dampak media sosial terhadap interaksi sosial pada remaja. Kami menggunakan pangkalan data google scholar dan artikel yang diterbitkan dalam SAGE dan Sciencedirect. Artikel dari berbagai pangkalan data dipilih menggunakan pendekatan Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Hasil analisis bahwa Media sosial dapat bermanfaat dan menguntungkan khususnya bagi remaja dan pelajar untuk pengembangan diri, mendapat informasi baru, menambah ilmu pengetahuan, menambah jejaring. Namun juga menciptakan jarak dengan individu disekitarnya hingga berpengaruh terhadap kesehatan mental remaja.Kata kunci: Sosial Media, Interaksi Sosial, Dampak Media Sosial, Remaja